Sex differences in the progression of cerebral microbleeds in patients with concomitant cerebral small vessel disease - Yoon, Cindy W.; Rha, Joung-Ho; Park, Hee-Kwon; Park, Soo-Hyun; Kwon, Soonwook; Kim, Byeong C.; Youn, Young Chul; Jeong, Jee Hyang; Han, Hyun Jeong; Choi, Seong Hye (Frontiers in Neurology, 2022)
Background and Purpose Sex differences in cerebral microbleeds (CMBs) are not well known. We aimed to assess the impact of sex on the progression of CMBs. Methods The CHALLENGE (Comparison Study of Cilostazol and Aspirin on Changes in Volume of Cerebral Small Vessel Disease White Matter Changes) database was analyzed. Out of 256 subjects, 189 participants with a follow-up brain scan were included in the analysis. The linear mixed-effect model was used to compare the 2-year changes in the number of CMBs between men and women. Results A total of 65 men and 124 women were analyzed. There were no significant differences in the prevalence (70.8% vs. 71.8%; P = 1.000) and the median [interquartile range (IQR)] number of total CMBs (1 [0-7] vs. 2 [0-7]; P = 0.810) at baseline between men and women. The median [IQR] increase over 2 years in the number of CMBs was statistically higher in women than in men (1 [0-2] vs. 0 [0-1], P = 0.026). The multivariate linear mixed-effects model showed that women had a significantly greater increase in the number of total, deep, and lobar CMBs compared to men after adjusting for age and the baseline number of CMBs (estimated log-transformed mean of difference between women and men: 0.040 (P = 0.028) for total CMBs, 0.037 (P = 0.047) for deep CMBs, and 0.047 (P = 0.009) for lobar CMBs). Conclusions The progression of CMB over 2 years was significantly greater in women than in men.